Plötzlicher Kindstod von zwei Säuglingen in Babytragehilfen - Storz, Dennis; Dame, Christof; Wendt, Anke; Gratopp, Alexander; Bührer, Christoph (Klinische Pädiatrie, 2021)
Sudden unexpected death in infancy (SUDI), previously termed sudden infant death syndrome (SIDS), is the second leading cause of death in infants beyond the neonatal period in Germany, and a major cause of infant mortality in economically well developed countries (OECD Health Statistics, 2019). The risk of SUDI peaks at the age of 2–4 months and then decreases continuously till the end of the first year. A complex multifactorial cause, rather than a single characteristic factor, may cause SUDI within a critical period of infant development (Guntheroth WG et al., Pediatrics 2002; 110: e64–e64). Risk factors include prematurity, male gender, bottle-feeding, prone sleeping position, overheating, as well as exposure to smoke amongst others (Carpenter RG et al., Lancet 2004; 363: 185–191). Thus, health professionals consistently advise and educate parents about avoidable risk factors of SUDI at routine well-baby examinations. Since the advent of SUDI prevention strategies in the 1980s, the incidence has decreased 10fold, from 1,55/1.000 live births in 1991 to 0,15/1000 in 2015. This number seems to have reached a steady state (Statistisches Bundesamt Germany, 2015).